Improving Indonesian Children’s Reading Skills through Virtual Reality Media: A Literature Review - Yenti, Yesni; Fitri, Trinindi Eriswan; Zahara, Leni; Putera, Rafhi Febryan; Azima, Nana Fauzana (Lectura : Jurnal Pendidikan, 2025)
In the era of Society 5.0, the integration of technology into education has become increasingly prevalent; however, its effectiveness in enhancing student learning processes, abilities, and outcomes remains a subject of debate. This study aims to explore the potential of Virtual Reality (VR) as a technological innovation to enhance motivation, understanding, and learning effectiveness in elementary education, particularly in the context of Society 5.0. This study employed a descriptive qualitative approach using a literature review-based research method. Data were collected and analyzed from various academic sources focusing on the use of VR in elementary education settings. The findings highlighted the significant potential of VR, particularly when integrated with artificial intelligence, to personalize learning, enhance student competencies, and assist teachers in developing intelligent and contextually relevant content. The literature also showed that VR implementation in elementary schools improves students’ motivation, conceptual understanding, and overall learning effectiveness. In conclusion, the application of VR in elementary education demonstrates strong potential as an innovative and adaptive learning tool in line with the goals of Society 5.0. Although challenges such as cost, infrastructure, and teacher readiness persist, the benefits of VR in fostering interactive and student-centered learning make it a valuable area for further research and development.